Perlindungan Hukum Terhadap Eksportir dan Importir dalam Transaksi Ekspor Impor Barang dengan Menggunakan L/C (Letter of Credit) Sebagai Alat Pembayaran - Nugraha, Bryan Artha; Andraini, Fitika (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of conducting research is to Know how to deal with strategies what to do to prevent it from happening irregularities in L/C and how form of legal protection if it occurs breach between the parties using L/C which is by method normative legal research concluded: The key to successful L/C handling is found in all parties involved, as it is prudence, thoroughness and discipline in handling every process that goes through. And to avoid it happening deviation in L/C, then it is necessary appropriate treatment strategy starting from before the opening of the L/C, request for opening L/C, after L/C opening, document handling, until with document delivery. Protection law is given to the parties to ensure security in transactions using L/C. If there are parties who feel aggrieved because the other party in agreement does not carry out its performance, then the aggrieved party will get legal protection according to regulation regarding good L/C in international law as well as national law. Protection is obtained from regulations that are generally regulates L/C namely Uniform Costums and Practice for Documentary Credit (UCP), Government Regulation No. 1 of 1982 concerning Export, Import and/or Implementation Foreign Exchange Flows, Bank Indonesia Regulations No. 5/11/PBI/2003 concerning Payment Import Transactions, and Government Regulation No. 29 of 2007 concerning Payment Methods and Delivery of Goods in Export Activities Import. The research results describe how the legal relationship between the customer and the issuing bank. L/C born from the L/C Issuance Application agreement. Agreement between customer and bank the publisher creates a legal relationship, namely the fulfillment of the rights and obligations of the parties in accordance with the L/C issuance agreement. Therefore the parties must fulfill the rights and obligation to avoid disputes.